Historical overview of the literature on business performance measurement from the beginning to the present - Zsidó, Kinga Emese (Applied Studies in Agribusiness and Commerce, 2015)
The paper summarizes the concept of business performance and the performance measurement. The concept of business performance has changed a lot over the past decades. The managers have understood that in order to achieve organizational goals, more emphasis should be placed outside the owners, on other market participants, on the stakeholders (eg: customers, clients, employees, suppliers and other partners, local communities, …). The ’90s are also called „The performance measurement revolution”, because a lot of new performance measurement methods, systems appeared. The performance measurements have the prominent role: to collect information about where we are going to achieve the goals, if needed for intervention.JEL code: B40